37OSubgroup analysis of IMpassion130: Atezolizumab + nab-paclitaxel (nab-P) in patients (pts) with advanced triple-negative breast cancer (TNBC) in Asian countries. (24th November 2019) - Iwata, H; Im, S-A; Sohn, J; Jung, K H; Im, Y-H; Lee, K S; Inoue, K; Tamura, K; Wong, A; Emens, L A; Barrios, C H; Adams, S; et al.
Abstract: Background: The global ph III IMpassion130 study (NCT02425891) in 1L mTNBC showed that PFS with atezolizumab (A) + nab-P (A+nab-P) was significantly better than with placebo (P) + nab-P in ITT and PD-L1 IC+ pts; clinically meaningful OS improvement was also seen in PD-L1 IC+ pts (Schmid et al. NEJM 2018, ASCO 2019). As region-specific differences have been reported for efficacy and toxicity of other therapies, we report outcomes for A+nab-P in IMpassion130 pts enrolled in Hong Kong, Japan, Singapore, South Korea, Taiwan, Thailand. Methods: Eligible pts with histologically documented advanced TNBC, ECOG PS 0-1 and tumour tissue for PD-L1 testing were randomised 1:1 to IV atezolizumab 840 mg or placebo on d1 and 15 (q2w) + nab-P 100 mg/m 2 on d1, 8 and 15 of a 28-d cycle until progression. Stratification factors were prior taxanes, liver mets and PD-L1 expression on tumour-infiltrating immune cells (IC, positive: ≥1%). Co-primary endpoints (EPs) were PFS (ITT and PD-L1+ pts) and OS (ITT and, if significant, PD-L1+ pts). Key secondary EPs were ORR and DOR. Results: As of 2 Jan 2019, median follow-up was 20.0 mo in 145 pts in Asian countries. In the A+nab-P (n = 79) and P+nab-P (n = 66) arms, respectively, 42% and 33% had prior (neo)adjuvant taxane treatment (tx), 29% and 17% had liver mets, and 43% and 35% were PD-L1 IC+. Efficacy data are in the table. As of 3 Sep 2018, all-cause, any-grade AEs occurred in 100% (G3-4, 44% and 39%) of safety-evaluable pts in the A+nab-P and P+nabP arms (n = 78, 65), respectively. Serious tx-related AEs occurred in 8% of A+nab-P and 6% of P+nab-P pts. G3-4 AEs of special interest occurred in 5% of A+nab-P and P+nab-P pts. Conclusions: In this post-hoc analysis, the efficacy of A+nab-P in IMpassion130 pts in Asian countries was consistent with the previously reported global ITT and PD-L1 IC+ pts. No new safety signals were observed, and tolerability was consistent with that of the overall population. Clinical trial identification: NCT02425891. Editorial acknowledgement: Medical writing assistance for this abstract was provided by Jonathan Lee, PhD, of Health Interactions, Ltd. and funded by F. Hoffmann-La Roche, Ltd. Legal entity responsible for the study: F. Hoffmann-La Roche, Ltd. Funding: F. Hoffmann-La Roche, Ltd. Disclosure: H. Iwata: Honoraria (self), Advisory / Consultancy: Chugai/Roche; Honoraria (self), Advisory / Consultancy: Novartis; Honoraria (self), Advisory / Consultancy: AstraZeneca; Honoraria (self), Advisory / Consultancy: Pfizer; Honoraria (self), Advisory / Consultancy: Lilly; Honoraria (self), Advisory / Consultancy: Daiichi-Sankyo. S-A. Im: Advisory / Consultancy, Research grant / Funding (institution): AstraZeneca; Advisory / Consultancy: Amgen; Advisory / Consultancy: Eisai; Advisory / Consultancy: Hanmi; Advisory / Consultancy: Ildong; Advisory / Consultancy: MediPactor; Advisory / Consultancy: Novartis; Advisory / Consultancy: Roche; Speaker Bureau / Expert testimony, Research grant / Funding (institution): Pfizer. J. Sohn: Research grant / Funding (self): MSD; Research grant / Funding (self): Roche; Research grant / Funding (self): Novartis; Research grant / Funding (self): AstraZeneca; Research grant / Funding (self): Lilly; Research grant / Funding (self): Pfizer; Research grant / Funding (self): Bayer; Research grant / Funding (self): GSK; Research grant / Funding (self): CONTESSA; Research grant / Funding (self): Daiichi Sankyo. K.H. Jung: Honoraria (self), Advisory / Consultancy: Roche; Honoraria (self), Advisory / Consultancy: AstraZeneca. K.S. Lee: Research grant / Funding (institution), Drug Supply: Dong-A Socio ; Advisory / Consultancy: Roche; Advisory / Consultancy: Novartis; Advisory / Consultancy: Lilly; Advisory / Consultancy: Pfizer. K. Inoue: Research grant / Funding (institution): Novartis; Honoraria (self), Research grant / Funding (institution): Pfizer; Honoraria (self), Research grant / Funding (institution): Chugai; Research grant / Funding (institution): Daiichi-Sankyo; Research grant / Funding (institution): Parexel/Puma Biotechnology; Research grant / Funding (institution): MSD; Research grant / Funding (institution): Bayer; Research grant / Funding (institution): Eli Lilly; Honoraria (self), Research grant / Funding (institution): Eisai. K. Tamura: Research grant / Funding (institution): Chugai. A. Wong: Research grant / Funding (institution): National Medical Research Council, Singapore; Research grant / Funding (institution): Otsuka Pharmaceuticals; Advisory / Consultancy: Novartis; Advisory / Consultancy: Pfizer; Travel / Accommodation / Expenses: Eisai. L.A. Emens: Honoraria (self): AbbVie; Honoraria (self): Amgen; Honoraria (self), Research grant / Funding (institution), Travel / Accommodation / Expenses: AstraZeneca; Honoraria (self), Travel / Accommodation / Expenses: Bayer; Research grant / Funding (institution), Travel / Accommodation / Expenses: Bristol-Myers Squibb; Honoraria (self): Celgene; Research grant / Funding (institution), Travel / Accommodation / Expenses: Genentech/Roche; Honoraria (self): Gritstone; Honoraria (self): Medimmune; Honoraria (institution), Travel / Accommodation / Expenses: Macrogenics; Travel / Accommodation / Expenses: Novartis; Honoraria (self): Peregrine; Honoraria (self), Travel / Accommodation / Expenses: Replimune; Honoraria (self): Syndax; Honoraria (self), Travel / Accommodation / Expenses: Vaccinex; Research grant / Funding (institution), Licensing / Royalties: Aduro Biotech; Research grant / Funding (institution): Breast Cancer Research Foundation; Research grant / Funding (institution): Corvus; Research grant / Funding (institution): Department of Defense; Research grant / Funding (institution): EMD Serono; Research grant / Funding (institution): HeritX, Inc.; Research grant / Funding (institution): Maxcyte; Research grant / Funding (institution): Merck; Research grant / Funding (institution): National Cancer Institute; Research grant / Funding (institution): NSABP Foundation; Research grant / Funding (institution): Translational Breast Cancer Research Consortium. C.H. Barrios: Advisory / Consultancy, Research grant / Funding (institution): Roche/Genentech; Advisory / Consultancy, Research grant / Funding (institution): Pfizer; Advisory / Consultancy, Research grant / Funding (institution): Novartis; Research grant / Funding (institution): Amgen; Advisory / Consultancy, Research grant / Funding (institution): AstraZeneca; Research grant / Funding (institution): Boehringer Ingelheim; Advisory / Consultancy, Research grant / Funding (institution): GlaxoSmithKline; Research grant / Funding (institution): Roche/Genentech; Research grant / Funding (institution): Lilly; Research grant / Funding (institution): Sanofi; Research grant / Funding (institution): Taiho Pharmaceutical; Research grant / Funding (institution): Mylan; Research grant / Funding (institution): Merrimack; Research grant / Funding (institution): Merck; Research grant / Funding (institution): AbbVie; Research grant / Funding (institution): Astellas Pharma; Research grant / Funding (institution): Biomarin; Research grant / Funding (institution): Bristol-Myers Squibb; Research grant / Funding (institution): Daiichi Sankyo; Research grant / Funding (institution): Abraxis; Research grant / Funding (institution): AB Science; Research grant / Funding (institution): Asana Biosciences; Research grant / Funding (institution): Medivation; Research grant / Funding (institution): Exelixis; Research grant / Funding (institution): ImClone Systems; Research grant / Funding (institution): LEO Pharma; Research grant / Funding (institution): Millennium; Advisory / Consultancy: Boehringer Ingelheim; Advisory / Consultancy: Eisai; Advisory / Consultancy: Bayer; Advisory / Consultancy: MSD. S. Adams: Research grant / Funding (institution): Genentech; Research grant / Funding (institution): Merck; Research grant / Funding (institution): Amgen; Research grant / Funding (institution): BMS; Research grant / Funding (institution): Novartis; Research grant / Funding (institution): Celgene. A. Schneeweiss: Honoraria (self), Research grant / Funding (institution), Travel / Accommodation / Expenses: Celgene; Honoraria (self), Speaker Bureau / Expert testimony, Research grant / Funding (institution), Travel / Accommodation / Expenses: Roche; Research grant / Funding (institution): AbbVie; Research grant / Funding (institution): Molecular Partner; Honoraria (self), Speaker Bureau / Expert testimony: AstraZeneca; Honoraria (self), Travel / Accommodation / Expenses: Pfizer; Honoraria (self): MSD; Honoraria (self): Tesaro; Honoraria (self): Lilly; Honoraria (self): Novartis. V. Diéras: Advisory / Consultancy: Roche/Genentech; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Lilly; Advisory / Consultancy: Novartis; Advisory / Consultancy: Daiichi Sankyo; Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: AbbVie; Advisory / Consultancy: Seattle Genetics; Advisory / Consultancy: Odonate. E.P. Winer: Honoraria (self): Lilly; Honoraria (self), SAB member and honoraria: LEAP; Honoraria (self): Genentech; Honoraria (self): Inifinite MD; Honoraria (self): Carrick Therapeutics; Honoraria (self): GSK; Honoraria (self): Jounce; Honoraria (self): Genomic Health; Honoraria (self): Merck; Honoraria (self): Seattle Genetics. S.Y. Chui: Full / Part-time employment: Roche/Genentech. V. Henschel: Shareholder / Stockholder / Stock options, Full / Part-time employment: Roche. H.S. Rugo: Research grant / Funding (institution): Pfizer; Research grant / Funding (self): Novartis; Research grant / Funding (institution): Lilly; Research grant / Funding (institution), Travel / Accommodation / Expenses: Genentech/Roche; Research grant / Funding (institution), Travel / Accommodation / Expenses: Macrogenics; Travel / Accommodation / Expenses: PUMA; Travel / Accommodation / Expenses: Mylan; Research grant / Funding (institution): Merck; Research grant / Funding (institution): OBI; Research grant / Funding (institution): Eisai; Research grant / Funding (institution): Plexxikon; Research grant / Funding (self), Travel / Accommodation / Expenses: Daiichi; Research grant / Funding (self): Immunomedics; Honoraria (self): Celltrion. S. Loi: Advisory / Consultancy, Research grant / Funding (institution), non-remunerated consultant: Novartis; Advisory / Consultancy, Research grant / Funding (institution), non-remunerated consultant: Bristol-Myers Squibb; Advisory / Consultancy, Research grant / Funding (institution), non-remunerated consultant: Roche/Genentech; Research grant / Funding (institution): PUMA Biotech; Research grant / Funding (institution): Eli Lilly; Advisory / Consultancy, Research grant / Funding (institution), non-remunerated consultant: Merck; Advisory / Consultancy, non-remunerated consultant: Seattle Genetics; Advisory / Consultancy, non-remunerated consultant: Pfizer; Advisory / Consultancy, Consulting fees paid to institution: Aduro Biotech. P. Schmid: Research grant / Funding (institution): AstraZeneca; Research grant / Funding (institution): Roche/Genetech; Research grant / Funding (institution): Oncogenex; Research grant / Funding (institution): Novartis; Research grant / Funding (institution): Astellas; Honoraria (self): Pfizer; Honoraria (self): Merck; Honoraria (self): Boehringer Ingelheim; Honoraria (self): Bayer; Honoraria (self): Eisai; Honoraria (self): Celgene; Honoraria (self): PUMA Biotech. All other authors have declared no conflicts of interest.